2023
DOI: 10.1177/10690727231173729
|View full text |Cite
|
Sign up to set email alerts
|

Invisibility and Negative Career Outcome Expectations among Racially and Ethnically Diverse College Students at a Predominantly White Institution

Abstract: The present study explored the relationship between invisibility experiences, a component of microaggressions, and negative career outcome expectations among a sample of Black, Indigenous, and People of Color (BIPOC) students attending a predominantly White institution of higher education (PWI). Additionally, given that invisibility is experienced differently across gender (i.e., intersecting invisibility), we explored whether the relationship between invisibility experiences and negative career outcome expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Additionally, intersectionality between ethnicity, family, and SES, particularly feelings of overachieving immigrant parents SES was endorsed by participants, similar to other studies (Koçak et al, 2021). Suh et al's (2024) findings were reflected by participants stating feelings about jobs where they did not feel represented appeared out of bounds.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Additionally, intersectionality between ethnicity, family, and SES, particularly feelings of overachieving immigrant parents SES was endorsed by participants, similar to other studies (Koçak et al, 2021). Suh et al's (2024) findings were reflected by participants stating feelings about jobs where they did not feel represented appeared out of bounds.…”
Section: Discussionsupporting
confidence: 80%
“…Several studies have shown how SIs interact with executive processing. For example, career decision self-efficacy was lower for students from high socioeconomic backgrounds (Turner et al, 2019), and others (Suh et al, 2024) have found that those from underrepresented racial/ethnic groups perceived fewer career options and more career barriers compared to Caucasians. In addition, mental health concerns such as worry (Hayden & Osborn, 2020) and depression (Anghel & Gati, 2021) are also associated with negative career thoughts.…”
Section: Executive Processingmentioning
confidence: 97%